What makes servant leadership effective for female employees? Servant leadership application during the COVID-19 pandemic - Fakhri, Mahendra; Raharja, Sam’UnJaja; Purnomo, Margo; Rivani, Rivani (International Journal of Innovative Research and Scientific Studies, 2024)
This study delves into the intricate dynamics of servant leadership and its profound impact on sustaining employee motivation amidst the unprecedented challenges posed by the COVID-19 pandemic. It sets out to meticulously examine and discern the pivotal factors that underpin the remarkable efficacy of servant leadership practices, particularly centered around female employees in an Indonesian setting, with a deliberate emphasis on women leaders. The research aims to understand the effectiveness of servant leadership among female employees in Indonesia, with a specific focus on women in leadership roles. The study includes a comprehensive sample of 310 respondents and utilizes confirmatory factor analysis within the Structural Equation Modeling-Partial Least Squares framework to determine the key factors influencing servant leadership effectiveness. The findings of the study suggest that one of the most influential factors in driving the effectiveness of servant leadership is helping subordinates grow and succeed. On the other hand, emotional healing has the least influential impact on enhancing servant leadership practices compared to other dimensions. The study’s findings provide valuable insights for organizations, especially in navigating the difficulties presented by the COVID-19 pandemic. Understanding the importance of fostering employees’ personal growth and success, as well as acknowledging the limited impact of emotional healing, can inform leadership approaches to sustain workforce motivation during times of uncertainty. These results highlight the significance of cultivating employees’ development within a framework of servant leadership, ultimately leading to a more resilient and motivated workforce, with particular relevance for female employees.